Daily Informal Multidisciplinary Intensive Care Unit Operational Debriefing Provides Effective Support for Intensive Care Unit Nurses. Issue 4 (July 2016) - Sandhu, Gagangeet; Colon, Jose; Barlow, Dawn; Ferris, Donna
Abstract : Background: Although most organizations have comprehensive formal stress management programs, an approach that is most likely to be helpful is the one that is curtailed specifically to the needs of a particular nursing unit. With that aim in mind, a process of daily intensive care unit (ICU) multidisciplinary operational debriefings was developed. These operational debriefings use the same concepts as traditional debriefing, yet are offered on a daily basis, rather than being reserved only for major stressful events. Furthermore, they are informal, brief (15 minutes), and multidisciplinary (intensivists, ICU nurses, chaplain, ICU social worker, ICU nutritionist, and ICU pharmacist). The purpose of this descriptive study was to determine the perceptions of attendees in relation to the implementation of daily operational debriefings. Methods: Six months into the process, the attendees were requested to fill out an anonymous voluntary survey. Questions were simple, straightforward, and close ended. Results: Of 47 potential respondents (42 nurses, 2 nurse managers, 1 social worker, 1 pharmacist, and 1 nutritionist), 42 completed the survey. Results revealed that an overwhelming majority felt that daily operational debriefings provide an effective unit-based support system, a sense of connectedness, and a commitment to the well-being of others. Nearly 50% of the respondents felt that the overall stress level in the ICU decreased, and 98% indicated operational daily debriefings should continue. Conclusion: Daily Informal multidisciplinary ICU operational debriefing provides an effective support system for ICU nurses. A modified model could be replicated for non-ICU units as well.